Digitalisasi Pembelajaran Menulis Paragraf Berbasis Media Padlet pada Kelas Perkuliahan - Nursalam; M Rais Salim; Israwati Amir; Abd. Rahim; Asia M; Suhartatik; Nurindah Purnama Sari (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Padlet serves as a digital board that can be used for writing paragraphs. The purpose of this research is to describe the phenomenon of digitalization in writing instruction using Padlet in university classes. This research is qualitative and adopts a case study approach. The data sources for this study are teachers and students from the Department of Religious Sociology at IAIN Ambon. The types of data in this research include verbal discourse and photo documentation of activities. The research instruments used are documentation guidelines, observation guidelines, and interview guidelines. The results of this research found that the implementation of digitalized paragraph writing instruction using Padlet consists of three stages: preparation, development, and conclusion. The preparation stage includes the analysis of needs, determining course objectives, content selection, material development, and technology selection. The development stage involves guidelines and instructions, Padlet media usage, writing and collaboration, discussions, and monitoring and support. The conclusion stage includes reflection, feedback, final evaluation, and closure.